Race on Display in 20th- and 21st Century France - Knox, Katelyn E. (Liverpool University Press, 2016)
In Race on Display in 20th- and 21st-Century France Knox turns the tables France's rhetoric of 'internal otherness', asking her reader not to spot those deemed France's others but rather to deconstruct the very gazes that produce them. Weaving together a vast corpus of colonial French children's comics, Francophone novels, and African popular music, fashion, and dance, Knox traces how the ways colonial 'human zoos' invited their French spectators to gaze on their colonized others still inform the frameworks through which racial and ethnic minorities are made-and make themselves-visible in contemporary France. In addition to analyzing how literature and music depicting immigrants and their descendants in France make race and ethnicity visible, Knox also illustrates how the works she analyzes self-reflexively ask whether they, as commodities sold within wider cultural marketplaces, perpetuate the culture of exoticism they seek to contest. Finally, Knox contends that to take seriously the way the texts interrogate the relationship between power, privilege, and the gaze also requires reconsidering the visions of normalcy from which racial and ethnic minorities supposedly depart. She thus concludes by exposing a critical 'blind spot' in French cultural studies-whiteness-before subjecting it to the same scrutiny France's 'visible minorities' face.